First record and a new species of Sericosura Fry & Hedgpeth, 1969 (Arthropoda: Pycnogonida: Ammotheidae) from a hydrothermal vent of Southwestern Indian Ridge - Wang, Jianjia; Huang, Dingyong; Shi, Xiaofeng; Lin, Rongcheng; Niu, Wentao (Zootaxa, 2018)
This is the first record of the genus Sericosura from the “Duanqiao” hydrothermal field on the Southwestern Indian Ridge. Collected material included two juvenile specimens temporarily assigned to S. bamberi and S. heteroscela respectively, and one male specimen with dimorphic legs here proposed as a new species, S. duanqiaoensis sp. nov. The discovery suggests potential connectivity among the hydrothermal vents of the Atlantic, Indian and Southern Oceans, expecting obtaining more specimens for further evolutionary studies to clarify the relationships of these hydrothermal vents.